The legal protection for women prisoners in Islamic law - Hussin, Nasimah; Abdul Majid, Wan Roslili (Serials Publications, 2014)
The infliction of imprisonment is not meant to deny the prisoner’s dignity as a human being but rather it is mainly for discipline and correction both of which objectives would be achieved by self reflection. Thus, the prisoners; men and women alike are entitled to have their fundamental rights fulfilled. They are also entitled to get equal treatment. Nevertheless, the women prisoners have special needs which require special consideration and attention. As far as Muslim women prisoners are concerned, they may have more specific needs since the treatment provided must always observe the Shari’ah ruling particularly in terms of food, clothing, performing religious duties etc. This paper examines the legal protection provided for women prisoners under Islamic law.